Práticas de cuidado em saúde mental na voz dos usuários de um centro de atenção psicossocial do Estado do Pará - CARDOSO, Márcia Roberta de Oliveira (Universidade Federal do Pará, 2018)
This paper aimed to analyze how practices of care in mental health are perceived by users of a Psychosocial Care Center (Caps) of the State of Pará. The methodology used was a qualitative approach, discursive and ethnographic. 14 registered users participated in the study in Caps. The interviews were analyzed according to themes: Health and Disease Process; Route Therapeutic; Care Practices in Mental Health; User and Autonomy. In speeches, the Caps was the site where users felt better care. It was observed the coexistence of care practices that corroborate the principles of Psychiatric Reform and others that still reproduce the asylum logic.